The Influence Of Full Day School On Student Learning Motivation Of VIII Class In SMPN 3 Raman Utara Lampung Timur 2018/2019 School Year. - Royadi Irwansyah; Syaiful M; Suparman Arif (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2019)
The aim of this research is to find out the effect of full day school on student learning motivation of VIII Class at SMPN 3 Raman Utara, East Lampung in 2018/2019 School Year. The research method used descriptive survey with method data collection techniques through observation, documentation, questionnaires and literature. The data analysis used qualitative data analysis technique. The results obtain based on existing data indicate there is an influence of Full Day School (FDS) on student learning motivation. This can be seen from the results of the calculation with the percentage of student motivation is 68.58% that meaning full day school giving good influence on student motivation in learning activities. Keywords: full day school, influence,  motivation to learn.